Human stem cell research: ethical and religious concerns over patenting biotechnological inventions in Malaysia - Abdul Ghani Azmi, Ida Madieha; Zawawi, Majdah (Kluwer Law International, 2015)
This chapter analyses the patentability of biotechnological inventions particularly those resulting from human embryonic stem cell research. The chapter puts forward the position that since the UK and Europe have considered ethics and morality as a factor in determining the patentability of biotechnological inventions, then Malaysia, in having adopted similar provisions into the patent laws in the country, could also rely on the ethical position to do the same. In doing so, the Islamic position would be relied on to provide an ethical basis for such a determination.